A Systematic Review of Neuromodulation Treatment Effects on Suicidality - Kucuker, Mehmet Utku; Almorsy, Ammar G.; Sonmez, Ayse Irem; Ligezka, Anna N.; Doruk Camsari, Deniz; Lewis, Charles P.; Croarkin, Paul E. (Frontiers in Human Neuroscience, 2021)
Introduction: Neuromodulation is an important group of therapeutic modalities for neuropsychiatric disorders. Prior studies have focused on efficacy and adverse events associated with neuromodulation. Less is known regarding the influence of neuromodulation treatments on suicidality. This systematic review sought to examine the effects of various neuromodulation techniques on suicidality. Methods: A systematic review of the literature from 1940 to 2020 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline was conducted. Any reported suicide-related outcome in reports were considered as a putative measure of treatment effect on suicidality. Results: The review identified 129 relevant studies. There was evidence that transcranial direct current stimulation was superior to sham in decreasing suicidal ideation in a randomized, controlled trial. Electroconvulsive therapy, magnetic seizure therapy, and repetitive transcranial magnetic stimulation treatments may decrease suicidality. There was limited literature focused on the potential protective effect of vagal nerve stimulation with respect to suicidal ideation. Data were mixed regarding the potential effects of deep brain stimulation on suicidality. Conclusions: Future prospective studies of neuromodulation that focus on the primary outcome of suicidality are urgently needed.